2022
DOI: 10.1371/journal.pone.0263611
|View full text |Cite
|
Sign up to set email alerts
|

Exploring non-physician care professionals’ roles in cancer multidisciplinary team meetings: A qualitative study

Abstract: The growing complexity of cancer care necessitates collaboration among different professionals. This interprofessional collaboration improves cancer care delivery and outcomes. Treatment decision-making within the context of a multidisciplinaire team meeting (MDTMs) may be seen as a particular form of interprofessional collaboration. Various studies on cancer MDTMs highlight a pattern of suboptimal information sharing between attendants. To overcome the lack of non-medical, patient-based information, it might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Nevertheless, some evidence shows that the inclusion of nursing personnel is viewed as less important [ 14 , 35 37 ]. Indeed, several authors have shown that the biomedical approach tends to take precedence over other points of view [ 15 , 35 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some evidence shows that the inclusion of nursing personnel is viewed as less important [ 14 , 35 37 ]. Indeed, several authors have shown that the biomedical approach tends to take precedence over other points of view [ 15 , 35 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous calls have been made to include more patient-centred information during MDTs [13][14][15]. The 2014 European policy statement on cancer MDTs emphasized that patients' treatment and care preferences should be discussed before making decisions [16].…”
Section: Why In Clude Non -Medic Al Patient Information and Patient V...mentioning
confidence: 99%
“…At the same time, their viewpoints and information are often given little weight in MDT decisions [30,31]. Nonphysicians and nurses also perceive that their information is not being heeded or adding to the decisions that are made [13,29,32]. Shifting the team dynamics to ensure that all patient information is presented, shifting roles as to who presents the information and/or changing mindsets about the value of bringing the patient perspective into MDT decisions could help to increase the likelihood that patient information is attended to in the recommendation.…”
Section: How S Hould Patient Information B E In Corp or Ated?mentioning
confidence: 99%
See 1 more Smart Citation
“…MDT meetings are often dominated by discussion among doctors rather than including other MDT members who may know the patient better or have a more patientcentred perspective, [11][12][13][14] creating a predominance of the biomedical model of disease. [15][16][17] This means that the stated aim of many MDT members-to have the patient central to the MDT treatment discussion-is at odds with the reality of the MDT process.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%